Remarks on the iconography of the engraved gem and cameos of Novae (Moesia Inferior) - Nowak, M. (Херсонесский сборник, 2006)
The collection of the Historical Museum of Svištov (Northern Bulgaria) includes at present 139 glyptic items, among them ten cameos. All of these come from the territory or the vicinity of Novae, a legionary camp established around the years 45–46 A.D., presumably by the 8th Legion (Augusta), which after Vespasian’s ascension to the throne was relocated to Gaul and replaced in Novae by the 1st Legion (Italian) in the year 69. With time Novae evolved from a legionary camp guarding the Lower Danubian limes into a Roman and early-Byzantine city, which existed until the 620s.